A line passes through (x1, y1) and (h, k). If slope of the line is m, show that k – y1 = m (h – x1).

Asked by Pragya Singh | 11 months ago |  84

Solution :-

Given: the slope of the line is ‘m’

The slope of the line passing through (x1, y1) and

(h, k) is $$\dfrac{ (k – y_1)}{(h – x_1)}$$

So,

$$\dfrac{ (k – y_1)}{(h – x_1)}$$ = m

(k – y1) = m (h – x1)

Hence proved.

Answered by Abhisek | 11 months ago

Related Questions

Find the angle between the line joining the points (2, 0), (0, 3) and the line x + y = 1.

Find the angle between the line joining the points (2, 0), (0, 3) and the line x + y = 1.

Prove that the points (2, -1), (0, 2), (2, 3) and (4, 0) are the coordinates of the vertices

Prove that the points (2, -1), (0, 2), (2, 3) and (4, 0) are the coordinates of the vertices of a parallelogram and find the angle between its diagonals.

Find the acute angle between the lines 2x – y + 3 = 0 and x + y + 2 = 0.

Find the acute angle between the lines 2x – y + 3 = 0 and x + y + 2 = 0.